Histamine H4 receptor antagonism prevents the progression of diabetic nephropathy in male DBA2/J mice. (February 2018) - Pini, Alessandro; Grange, Cristina; Veglia, Eleonora; Argenziano, Monica; Cavalli, Roberta; Guasti, Daniele; Calosi, Laura; Ghè, Corrado; Solarino, Roberto; Thurmond, Robin L.; Camussi, Giovanni; Chazot, Paul L.; et al.
Graphical abstract: Abstract: Due to the incidence of diabetes and the related morbidity of diabetic nephropathy, identification of new therapeutic strategies represents a priority. In the last few decades new and growing evidence on the possible role of histamine in diabetes has been provided. In particular, the histamine receptor H4 R is emerging as a new promising pharmacological target for diabetic nephropathy. The aim of this study was to evaluate the efficacy of selective H4 R antagonism by JNJ39758979 on the prevention of diabetic nephropathy progression in a murine model of diabetes induced by streptozotocin injection. JNJ39758979 (25, 50, 100 mg/kg/day p.o.) was administered for 15 weeks starting from the onset of diabetes. Functional parameters were monitored throughout the experimental period. JNJ39758979 did not significantly affect glycaemic status or body weight. The urine analysis indicated a dose-dependent inhibitory effect of JNJ39758979 on Albumin-Creatinine- Ratio, the Creatinine Clearance, the 24 h urine volume, and pH urine acidification ( P < 0.05). The beneficial effects of JNJ39758979 on renal function paralleled comparable effects on renal morphological integrity. These effects were sustained by a significant immune infiltration and fibrosis reduction. Notably, megalin and sodium-hydrogen-exchanger 3 expression levels were preserved. Our data suggest that the H4 R participates in diabetic nephropathy progression through both a direct effect on tubular reabsorption and an indirect action on renal tissue architecture via inflammatory cell recruitment. Therefore, H4 R antagonism emerges as a possible new multi-mechanism therapeutic approach to counteract development of diabetic nephropathy development.